Testing the neurocognitive model of antidepressant treatment - Warren, M (2016)
The neurocognitive model of antidepressant treatment action states that antidepressants work by producing relatively immediate positive shifts in emotional processing, which translate into clinical improvement with time. Short-term or even acute doses of antidepressants can, for example, increase memory for positive self-referent words or decrease amygdala activation to fearful faces, and these early changes correlate with later clinical improvement. However, there are a number of ways in which the model needs further probing. The aim of this thesis was to test the neurocognitive model by: 1) investigating whether changes in emotional processing occur in an antidepressant with a novel mechanism of action, St John’s wort, as the model predicts; and 2) examining whether there is a comparable pattern of neuropsychological changes to citalopram in a population of high neurotic volunteers, whose baseline emotional biases may make them a more ideal group in which to study drug effects. We found that seven days of St John’s wort produced similar changes to other antidepressants, for example reducing recognition of disgusted faces and attention to fearful faces while increasing memory for positive words. The drug did not affect other aspects of cognition including working memory and reward learning. These findings support the theory that early psychological changes are a common feature of all antidepressants. On the other hand, four weeks of citalopram treatment produced apparently contradictory effects in high neurotics, increasing memory for positive words but also increasing recognition of negative facial expressions. Neuroimaging data showed that high neurotics had greater response to neutral faces in emotional processing areas compared to low neurotics, which was reduced with citalopram. High neurotics also showed increased resting state connectivity in default mode network areas and between amygdala and cortical areas, which was again reduced with citalopram. We suggest that in this group citalopram corrects general negative emotional processing biases, but also works to decrease a natural aversion to particularly threatening socially-relevant stimuli. Overall this thesis supports the idea that early changes in emotional processing are vital for antidepressant action, but also suggests that in certain groups such as high neurotics, some changes may be more nuanced than previously reported and warrant further scrutiny.